2022
DOI: 10.1093/ofid/ofac492.991
|View full text |Cite
|
Sign up to set email alerts
|

1153. Safety and Potential Efficacy of Exosomes Overexpressing CD24 (EXO-CD24) for the Prevention of Clinical Deterioration in Patients with Moderate or Severe COVID-19: A Phase II, Randomized, Single-blinded Study.

Abstract: Background EXO-CD24 is a novel inhaled drug of exosomes displaying CD24, a protein with anti-inflammatory properties. We evaluated the safety and potential efficacy of EXO-CD24, in a phase II, randomized, single-blinded clinical trial of EXO-CD24 in hospitalized patients with moderate or severe COVID-19, following the preliminary safety and efficacy results of a phase 1 study (ClinicalTrials.gov: NCT04747574). Methods Two ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also, 72 patients experienced at least a 50% reduction in inflammatory index levels from baseline (admission) by day 7. Further, no treatment-related adverse events were reported [228].…”
Section: Clinical Trials Of Extracellular Vesicles In Covid-19mentioning
confidence: 93%
“…Also, 72 patients experienced at least a 50% reduction in inflammatory index levels from baseline (admission) by day 7. Further, no treatment-related adverse events were reported [228].…”
Section: Clinical Trials Of Extracellular Vesicles In Covid-19mentioning
confidence: 93%
“…Furthermore, depending on the bioactive cargos, exosomes also contribute to a broad range of disease physiology and pathogenesis, including inflammation, cancer, neurological diseases, autoimmunity, metabolic disorders, etc. [1,5].…”
Section: Exosomementioning
confidence: 99%
“…As a result, EVs have been applied in the treatments for several types of diseases, such as cancers and neurological diseases. For example, a result from a recent phase II clinical trial has also shown an inhalable CD24-expressing exosome drug, which can potentially suppress inflammatory cytokine storm, can improve both respiratory rate (83.7%) and pulse oximetry (64%) in COVID-19 patients [5].…”
Section: Introductionmentioning
confidence: 99%